AB1012 INVESTIGATION OF RELATIONSHIP BETWEEN SEXUAL FUNCTION AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY IN PATIENTS WITH BEHÇET'S: PRELIMINARY STUDY. (2nd June 2020) - Ayan, A.; Kucuk, M. F.; Cetin, S. Y.; Erol, M. K.
Abstract : Background: Patients with Behçet's have sexual dysfunction in recently literature. However, depression and anxiety accompanying these studies were not excluded. In addition, increased sexual dysfunction in patients with Behçet's has been reported in these studies in relation to depression and anxiety. Also it has been stated that endothelial dysfunction decreases the vasodilator neurotransmitter level. It was emphasized that this may lead to erectile dysfunction in disease of Behçet's. Objectives: The aim of this study is to evaluate the relationship between erectile dysfunction (ED) and radial peripapillary capillary (RPC) density determined by Optical Coherence Tomography Angiography (OCTA). Methods: Patients under 45 years old who had no known additional disease and had no eye and neurological involvement were included in the study. The patients were evaluated with Beck Depression and Anxiety Scale. Accordingly, patients without anxiety and depression were included in the study. An International Index of ErectileFunction (IIEF) questionnaire was applied to a total of 18 patients who met the inclusion criteria. Detailed ophthalmological examination and OCTA imaging were performed by the ophthalmologist. Patients whose eye bottom could not be evaluated clearly (Corneal pathology, cataracts, etc.), image quality was 0.5 and below, and additional eye disease (glaucoma, optic neuropathy, maculopativb) were excluded from the study. Results: The mean age of the patients was 37 ± 6.5 years, and the duration of the disease was 82.37 ± 47.78 months. There was a strong relationship between RPC Small Vessel Whole Density (RPC-SVWD) and overall satisfaction and sexual satisfaction (p: 0.036 and 0.045). There was a strong positive relationship between RPC Small Vessel Peripapillary Density (RPC-SVPD) and erectile function, sexual desire, sexual satisfaction and general satisfaction (p: 0.036, 0.032, 0.005, 0.004). There was a strong positive relationship between RPC All Vessel Peripapillary Density (RPC-AVPD) and erectile function and sexual satisfaction (p: 0.048, 0.015). Conclusion: In our study, a significant relationship was found between sexual function and RPC density. In the literature, it has been found that nitric oxide synthesis decreases due to endothelial dysfunction in patients with Behçet's. Although there are preliminary study data, we found a significant relationship between the vascular layer of both the penis and the eye in our study. The data we obtained in this study, in which all factors that may cause erectile dysfunction are excluded, show that Behçet's, which is theoretically known to affect all vascular structures, can affect sexual functions by its nature. In our study, although there is a relationship between ED and OCTA data in Behçet's disease, the large number of cases of our ongoing study will provide clearer information. References: [1]Erdemir F, Atilgan D, Boztepe Ö, Aytan P, Uluocak N, Taliyurt T. Is there a relationshipbetween Behçet disease and erectile dysfunction? Turkish Journal of Urology 2010; 36:380-386. [2]Rosen RC, Riley A, Wagner G Osterloh IH, Kirkpatrick J, Mishra A. The international index of erectilefunction (IIEF): a multidimensional scale for assesment of erectile dysfunction. Urology 1997; 49: 822–830. [3]Validation Group of Turkish Society of Andrology. International Index of Erectile Function (IIEF) Turkish version, 4th National Sexual Dysfunction Congress Abstract Book, pp 43, 2002. [4]Örem A, Ertürk M, Cimşit G, Kural BV. Effect of plasma from patients with Behçet disease on the production of nitricoxide in cultured human umbilical vein endothelial cells. Med Princ Pract 2004;13:35-8. Disclosure of Interests: None declared